ON THE PROBLEM OF THE NUMERICAL MODEL CONSTRUCTION OF ZERO-AGE SUBSTARS - Zakhozhaj, V. A.; Blokhina, M. D.; Pysarenko, A. I.; Yatsenko, A. A.; Slusarenko, Yu. V. (Одеські астрономічні публікації, 2017)
The numerical modelling of substars inner structure is analysed and main definitions are suggested. Here we present results of calculation of degeneracy parameter ψ, permitting to make calculate the dependence of number of free electrons on function temperature and density typical interior of zero-age substars (ZAS).